Utilización del Google Classroom como apoyo al proceso educativo de la Matemática en la U.E “11 de Noviembre - Cando Cando, Margoth Yolanda (2024)
The present research entitled "Use of Google Classroom as a support to the educational process of mathematics in the U.E "11 de Noviembre" aims to analyze the importance of Google Classroom as a support to the educational process of mathematics in the Educational Unit "11 de Noviembre", the research was carried out during the academic period 2023-2024. The methodology used a quantitative approach with a non-experimental design, descriptive level, and a type of cross-sectional, field, and bibliographic study. The population was considered to be the eighth-year EGB students of the Educational Unit "11 de Noviembre", taking as a sample a non-probabilistic intentional sampling to whom the technique of a survey was applied, allowing the collection of direct data with its instrument, the questionnaire. Considering the results obtained, we can denote that the search of teachers regarding the management of their classes can be amplified, keeping in mind the need to impact from pedagogical practice to lead students to learning goals that contribute to the construction of knowledge through new technologies. It is recommended that the students' perceptions regarding the methodological development of classroom practices be worked on, considering that these can contribute to the improvement of classroom actions by educators.